ANALISIS TINJAUAN LITERATUR TENTANG MENINGKATKAN SEMANGAT DAN PRESTASI BELAJAR KOGNITIF MELALUI PENERAPAN MODELDISCOVERY LEARNING - I Gede Windrawan; Lukman El Hakim; Rizhal Hendi Ristanto (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
The objective of this study is to provide an overview of relevant literature regarding the enhancement of motivation and cognitive learning achievements among high school students in physics courses through the implementation of the Discovery Learning model. The research employs qualitative methods with a focus on literature review. The research process involves stages such as collecting, screening, presenting, discussing, and drawing conclusions from papers. The primary data source for this study comprises national journal articles published over the last five years (2018 to 2023). Among the identified articles, 10 out of 16 were found to align with the specified thematic focus. The application of the Discovery model in high school physics classes is executed in accordance with the referenced theoretical framework. Consequently, the implementation of the Discovery Learning model is shown to have a positive impact on increasing both motivation and cognitive learning outcomes for high school students in physics classes.